Hubungan Hasil Belajar Mata Kuliah Kepemimpinan Dengan Karakter Building (Mandiri) Mahasiswa - Andika Tio Candra; Fauzan Khalis; Fatma Tresno Ingtyas; Laurena Ginting (Badan Penerbit STIEPARI Press, 2026)
This study aims to investigate the relationship between academic achievement in the Leadership course and student character development, particularly in the aspect of independence, among Culinary Arts Study Program students of the class of 2023 at Medan State University. The method used in this study is a quantitative approach with a correlational design, involving 60 participants with a saturated sampling technique. Data collection was carried out through documentation of academic grades and a questionnaire consisting of 10 statements with a four-point Likert scale. The results of the validity test showed that all items were valid with correlation values between 0.818 and 0.932, while the reliability test showed a Cronbach’s Alpha value of 0.972, indicating very good consistency. The data were also normally distributed and the relationship between variables showed linear properties. Through the Pearson correlation test, an r value of 0.923 was obtained with a significance level of 0.01, which indicates a very strong and significant relationship between learning outcomes, leadership and student independence character. These findings underscore that leadership learning plays a vital role in instilling the values of responsibility, discipline, and independence in students, as well as strengthening aspects of character development in higher education as preparation for the world of work and social interaction.